Criminological Research and the Death Penalty: Has Research by Criminologists Impacted Capital Punishment Practices? - Waldo, Gordon P. (American journal of criminal justice, 2019)
At the request of the SCJA president this paper addresses five questions. Does criminological research make a difference relative to the death penalty? - If criminological research does make a difference, what is the nature of that difference? - What specific instances can one cite of research findings influencing death penalty policy decisions? Why hasn’t our research made more of a difference? What can we do, either in terms of directing our research or in terms of disseminating it, to facilitate it making a difference? Specific examples of research directly impacting policy are examined. The evidence presented suggests that research on capital punishment has had some impact on policy, but not nearly enough. There is still a high level of ignorance that has limited the impact of criminological research on death penalty policy. The proposed solution is to improve the education of the general public and decision makers in order to increase the impact of criminological research on capital punishment policy.